Effects of drain depth of vertisols, nitrogen source and time of application on nutrient uptake by maize (Zea mays L.) in Western Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2017)
Nitrogen is the most limiting plant nutrient in Vertisols in western Ethiopia. Vertisols properties and management factors as well as fertilizer source and time of application could influence nutrient uptake by crops. With this view, a field study was conducted at Ambo Agriculture Research Centre experimental site during the main cropping season of 2013- 2014, with the aim to determine interactive effects of drain depth of Vertisols, N source and time of N application on nutrient uptake by maize. Treatments comprised five drain depths (0, 15, 30, 45 and 60 cm), two N sources (urea and ammonium sulfate) and two timings of N applications (twice and thrice). The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. Result showed that there was significant interactions effect of drain depths, N source and time of application on the concentration of nutrients in the grain and stover. The NH4-N uptake by maize was found to be significantly better than NO3-N utilization by maize. Grain and stover uptake of N, P and K by maize increased with drain depth and thrice split application of ammonium sulfate. It is concluded that draining off excess soil water from the rhizosphere is the key factor in improving nutrient uptake by maize in Vertisols in Ambo area.Int. J. Agril. Res. Innov. & Tech. 7 (1): 1-7, June, 2017